Spatial Pattern of Male-Female Literacy Differential in Asansol City (Paschim Bardhaman, West Bengal): A Ward Level Geographical Study - Usha Kiran Tudu; Sikandar; V.K. Tripathi (National Geographical Journal of India, 2022)
Literacy is an important tool in enhancing the quality of life. Present paper is an attempt to analyse the ward level spatial pattern of male-female literacy differential based on secondary data. The city is divided into fifty wards which occupies an area of 127.87 square kilometres. The average literacy rate of Asansol city is 78.85 per cent. Literacy differential index by Prof. R. P. Mishra has been used to study the literacy differential. The literacy differential of Asansol city is 0.124 which varies between highest in ward no. 37 (0.368) to lowest in ward no. 01 (0.066) indicating a substantial disparity in the gap between male and female literacy in different wards. Asansol is a coal and iron based industrial hub and industrial workers constituted the substantial portion of the population who gives less preference to education, especially to female education which is the main reason for these differences.